Forehand footwork variability in the attacking situation at elite level - Conde Ripoll, R.; Genevois, C. (Coaching and Sport Science Review, 2022)
The aim of the present study was to analyze the different patterns of forehand footwork in attacking situation at elite level. 498 forehand shots played during rallies and involving forward momentum of the body during the final draw of the US Open tournament held in 2019 and 2021 were analyzed. The results highlighted 6 main footwork patterns involving distinct roles for the front leg and the back leg. In conclusion, technical analysis should consider the dynamic aspect of strokes and coaches should work on the variability of footwork in player development.